2010
DOI: 10.1155/2010/319128
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Fluency Deficits Co-Occur with Memory Deficits in Geriatric Patients at Risk for Dementia: Implications for the Concept of Mild Cognitive Impairment

Abstract: Abstract. We tested the notion that patients at high risk for progression to Alzheimer's disease (AD) display relatively isolated memory deficits by assessing the relationship between memory and fluency performances in a sample of 92 geriatric subjects with cognitive complaints and normal to mild clinical presentations. Patient groups were formed on the basis of memory test scores. Patients with normal memory scores also performed normally on fluency tests, and their fluency scores were significantly higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
(61 reference statements)
2
20
0
Order By: Relevance
“…However, impairment in semantic fluency, with relative sparing of phonemic fluency, also occurs. 27,28 This observation is attributed to the fact that temporal cortex, one of the first brain regions affected in AD, 29,30 plays a larger role in mediating semantic than phonemic verbal fluency. 31 In contrast, early cognitive deficits in PD usually involve attention and frontal-executive function mediated in part by cortical-striatal dopamine deficiency, though some patients do initially exhibit isolated deficits in other domains.…”
Section: Discussionmentioning
confidence: 99%
“…However, impairment in semantic fluency, with relative sparing of phonemic fluency, also occurs. 27,28 This observation is attributed to the fact that temporal cortex, one of the first brain regions affected in AD, 29,30 plays a larger role in mediating semantic than phonemic verbal fluency. 31 In contrast, early cognitive deficits in PD usually involve attention and frontal-executive function mediated in part by cortical-striatal dopamine deficiency, though some patients do initially exhibit isolated deficits in other domains.…”
Section: Discussionmentioning
confidence: 99%
“…The semantic fluency task requires attention, information retrieval, and intact semantic associations [35–37], and is strongly dependent upon the hippocampus and related structures in the left mediotemporal lobe [38, 39]. In patients with AD, semantic fluency positively correlates with measures of memory [40] and the ability to perform everyday activities [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Verbal fluency tests have the advantages of ease and brevity of administration, which make them suitable as bedside tests for assessment of possible cognitive decline . Semantic verbal fluency (retrieval of words in a specified category, e.g., animals) and phonemic fluency (retrieval of words starting with a specified letter of the alphabet) both reflect executive functioning, and frontal lesions impair performance on both tests to a similar degree, but semantic tests have an additional semantic memory component, and temporal lobe lesions such as those in AD result in greater impairment in semantic fluency than in phonemic fluency .…”
mentioning
confidence: 99%
“…Studies of relative semantic‐phonemic discrepancies in MCI have yielded discordant results. Most studies have demonstrated poorer semantic than phonemic fluency in individuals MCI than in normal controls, but others have shown similar patterns in phonemic‐semantic verbal fluency discrepancy scores in individuals with amnestic MCI and controls, although these studies were limited by small sample size. Whether discrepancy scores are useful in predicting who will progress to AD has not been well studied.…”
mentioning
confidence: 99%